Aggregating farmers for markets and agricultural support services - Tuyishime, Norbert (Technical Centre for Agricultural and Rural Cooperation, 2018)
Agriculture is back at the top of Africa's development agenda, enjoying the support of governments and attracting heavy investments from private sectors. Many of smallholder farmers across Africa that are central to the agricultural transformation taking shape on the continent, however, struggle to benefit from these developments due to their dispersed, small-scale and unorganized nature. Aggregation of smallholder farmers' needs may provide the solution, says Norbert Tuyishime of the Eastern Africa Farmers Federation (EAFF).